Emerging trends in the recovery of ferrospheres and plerospheres from coal fly ash waste and their emerging applications in environmental cleanup - Yadav, Virendra Kumar; Modi, Timsi; Alyami, Abeer Yousef; Gacem, Amel; Choudhary, Nisha; Yadav, Krishna Kumar; Inwati, Gajendra Kumar; Wanale, Shivraj Gangadhar; Abbas, Mohamed; Ji, Min-Kyu; Jeon, Byong-Hun (Frontiers in Earth Science, 2023)
Coal fly ash (CFA) is a major global problem due to its production in huge volumes. Fly ash has numerous toxic heavy metals; thus, it is considered a hazardous material. However, it also has several value-added minerals like ferrous, alumina, and silica along with other minerals. Fly ash also has several natural micro- to nano-structured materials; for instance, spherical ferrous-rich particles, cenospheres, plerospheres, carbon nanomaterials, and unburned soot. These micron- to nano-sized particles are formed from the molten slag of coal, followed by condensation. Among these particles, plerospheres which are hollow spherical particles, and ferrospheres which are ferrous-rich particles, have potential applications in the environmental cleanup, research, catalytic industries, and glass and ceramics industries. Additionally, these particles could be further surface-functionalized or purified for other applications. Moreover, these particles are widely explored for their potential in the army and other defense systems like lightweight materials and sensing The recovery of such particles from waste fly ash will make the process and remediation technology economically and environmentally friendly. The current review focuses on the various structural and elemental properties of ferrospheres and plerospheres from fly ash. This review also focuses on the emerging applications of both naturally formed materials in CFA.